INFLUENCE OF PATHOGENIC ATTACK ON VINE VARIETIES OF CABERNET SAUVIGNON ON THE CONTENT OF TRANS-RESVERATROL IN WINE - DIMITAR R. DIMITROV; EMIL B. BALASHKOV; DUSHKO D. NEDELKOVSKI; YORDANKA G. BELBEROVA 2 (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A study of the impact of pathogenic attack on vine varieties of Cabernet Sauvignon on the content of trans-resveratrol in wine was carried out. Some of the vines were attacked by two pathogens: Botrytis cinerea - a cause of "gray mold"; Phyllosticta ampelicida (asexual phase from Guignardia bidwellii) - the causer of "black rot". It was found that when Botrytis cinerea attacked the vines with high degree (93 %) and index (50.33) (variant V1), this reflected in lower levels of established trans-resveratrol in wine (3.23 mg∙dm-3), in compared to control pathogen-free V2 variant (3.74 mg∙dm-3). The same trend was observed in the attack of the other pathogen. Phyllosticta ampelicida (asexual phase from Guignardia bidwellii), even in low attack degree (10 %) (variant V4) and index (2.5), resulted in lower levels of trans-resveratrol in wine (2.34 mg∙dm-3), compared to control pathogen-free variant V3 (2.56 mg∙dm-3). The study found a lower content of trans-resveratrol in wine produced from grapes of organically grown vines compared to that of conventionally grown.